Overuse of non-prescription analgesics by dental clinic patients - Zallen Richard D; Bogdan Gregory M; Dart Richard C; Ries Nicole L; Heard Kennon J; Daly Frank (BMC, 2008)
Abstract Background Many patients present to dental clinics for treatment of painful conditions. Prior to seeking treatment, many of these patients will self-medicate with non-prescription analgesics (NPA), and some will unintentionally overdose on these products. The objective of this study is to describe the use of NPA among dental patients. Methods All adult patients presenting to an urban dental clinic during a two-week period in January and February of 2001 were approached to participate in this research project. Trained research assistants using a standardized questionnaire interviewed patients. Patient demographics and the NPA usage over the 3 days preceding the office visit were recorded. We defined a supra-therapeutic dose as any dose greater than the total recommended daily dose stated on package labeling. Results We approached 194 patients and 127 participated. The mean age of participants was 35.5 years, 52% were male. Analgesic use preceding the visit was reported by 99 of 127 patients, and most (81/99) used a NPA exclusively. Fifty-four percent of NPA users were taking more than one NPA. NPA users reported using ibuprofen (37%), acetaminophen (27%), acetaminophen/aspirin combination product (8%), naproxen (8%), and aspirin (4%). Sixteen patients reported supra-therapeutic use of one or more NPA (some ingested multiple products): ibuprofen (14), acetaminophen (3), and naproxen (5). Conclusion NPA use was common in patients presenting to a dental clinic. A significant minority of patients reported excessive dosing of NPA. Ibuprofen was the most frequently misused product, followed by naproxen and acetaminophen. Though mostly aware of the potential toxicity of NPA, many patients used supra-therapeutic dosages.